Strengthening locally led agricultural policy analysis capacity: Lessons from experience - Jayne, Thomas S.; Babu, Suresh Chandra; Boughton, Duncan; Hendriks, Sheryl L.; Mkandawire, Elizabeth; Dorosh, Paul A.; Savadogo, Kimsey (Michigan State University, 2019)
Agricultural policies affect almost everyone in the world, directly or indirectly. Improvements in agricultural policy analysis capacity can therefore significantly benefit society. Based on the full report, this brief summarizes lessons learned from the Food Security Policy Innovation Lab’s capacity strengthening efforts over the 2013-2018 period and from related capacity development initiatives conducted over the last four decades by the partner institutions in Africa and Asia. “Capacity” is defined as the resources required for people and institutions to reach their objectives and achieve results in an efficient and sustainable manner. Capacity development is therefore the process of enhancing, improving, and unleashing such resources – in people, organizations, and systems. In this report, the term “locally led” refers to institutions registered in the host country, led by nationals of the host-country and often, but not necessarily, affiliated with a public university or government unit in the host country.